198 Current provision of general practitioner services in or alongside emergency departments in England. Issue 12 (23rd November 2020) - Brant, Heather; Voss, Sarah; Cooper, Alison; Edwards, Michelle; Price, Delyth; Gaughan, James; Edwards, Adrian; Benger, Jonathan
Abstract : Aims/Objectives/Background: One approach to addressing increasing demand in emergency departments (EDs) has been the co-location of general practitioners (GPs) in or alongside the emergency department (ED), known as GPED. This approach was both advocated by the National Health Service (NHS) and supported by capital funding in 2017. However, little is known about the models of GPED that have been implemented as a result. Methods/Design: We collected data on the model of GPED in use (if any) at 163/177 (92%) of type one EDs in England at two time points: September 2017 and December 2019. Multiple data sources were used including: on-line surveys; interviews; case study data; publicly available information. Models were classified according to an iteratively developed taxonomy as Inside/integrated, Inside/parallel, Outside/onsite, Outside/offsite. Results/Conclusions: The proportion of EDs using GPED increased from 81% to 95% over the study period. The most common model was 'Inside/parallel' to the ED: 30% (44/149) in 2017, rising to 49% (78/159) in 2019. The number of Inside/integrated models dropped from 26% (38/149) to 9% (15/159). 23 sites commenced and four sites ceased GPED provision. 87% (142/163) of the EDs sampled were awarded capital funding. We identified no association between the type of GPED model adopted and the observable characteristics of EDs such as annual attendance, rurality of location and deprivation within the population served. The majority of EDs in England have now adopted GPED. The increase in Inside/parallel models and the reduction in Inside/integrated models is likely to be related to the availability of capital funding to finance structural changes to EDs so that separate GP services could be provided. Further research is required to understand the relative effectiveness of the various models of GPED identified.